Indonesia’s Constitutional Identity: A Comparative Study of Islamic Constitutionalism - Nggilu, Novendri Mohamad; Wahidullah, Wahidullah; Noviawati, Evi; Ismail, Dian Ekawaty (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
Constitutionalism in Muslim-majority countries faces the challenge of balancing the application of Islamic principles with modern values in the context of the nation-state. This research aims to analyse how Indonesia’s constitutional identity, based on the pluralistic Pancasila, differs from other Muslim-majority countries such as Egypt, Pakistan, and Iran, emphasising Sharia as the foundation of law. Using statutory, historical, and comparative approaches, this research finds that the Indonesian model creates a unique harmony between religious pluralism and Islamic values, different from the dominant theocratic. The novelty of this article is its comparative analysis of constitutional identities in Muslim-majority countries, particularly emphasising Indonesia's unique pluralistic model. In contrast to Egypt, Pakistan, and Iran, which incorporate Islamic principles to varying extents, Indonesia adopts a Pancasila-based approach that integrates religious values within an inclusive, pluralistic framework. This model illustrates how religious values coexist with democratic principles and human rights. The study positions Indonesia as a potential model for balancing nationalism, religious diversity, and modern legal frameworks, providing valuable lessons for other Muslim-majority countries facing similar challenges.